Implementasi Building Information Modeling (BIM) terhadap Mutual Check 100 pada Pekerjaan Struktur Proyek Rusun Asrama Polisi Pingit Yogyakarta - Sianturi, Niel Tamsoju; Pahang Putra, I Nyoman Dita (Jurnal Talenta Sipil, 2024)
Along with the development of Industry 4.0 technology, Building Information Modeling (BIM) has emerged as an innovation in planning, designing, and executing construction projects. BIM is a technological concept with methods and workflows based on project work information, all integrated into a digital model, which is then translated into a three-dimensional representation to enhance building design and construction productivity. In the Police Dormitory Apartment Project in Pingit, the need for quick and accurate calculations, cost projections, and volume of structural work is crucial. This can be easily realized through the application of Tekla Structures Building Information Modeling (BIM). It is expected that there will be a clear depiction of how BIM-based construction technology can be effectively utilized in this project. The method used is the BIM method with Tekla as the supporting software. From this modeling, it was found that the total cost of foundation work had a cost difference of IDR 19.973.729,42, which is 1,63%; the total cost of pedestal column work had a cost difference of IDR 13,713,600.03, which is 6,37%; and the total cost of sloof work had a cost difference of IDR 14.423.328,99, which is 6,06%. The total cost difference for all structural work on the foundation, sloof, and pedestal column was IDR 48.110.658,44, which is 2.86%. This suggests that the cost calculations using Tekla Structures are smaller compared to the MC100 work quantity.